Estimation of the incidence of bacterial vaginosis and other vaginal infections and its consequences on maternal/fetal outcome in pregnant women attending an antenatal clinic in a tertiary care hospital in North India - Lata Indu; Pradeep Yashodhara; Sujata; Jain Amita (Wolters Kluwer Medknow Publications, 2010)
Aims: This study was undertaken to estimate the incidence of bacterial vaginosis (BV) and other vaginal infections during pregnancy and its association with urinary tract infections (UTI) and its consequences on pregnancy outcome, maternal and fetal morbidity and mortality. Settings and Design: Prospective cohort study. Materials and Methods: The present prospective cohort study was conducted on 200 women attending the antenatal clinic (ANC) of a tertiary hospital. All pertinent obstetric and neonatal data covering antenatal events during the course of pregnancy, delivery, puerperium and condition of each newborn at the time of birth were collected. BV was detected by both Gram stain and gold standard clinical criteria (Amsel′s composite criteria). Statistical analysis used: Data were analyzed using SPSS version 9. Fischer′s exact test, chi square tests and Student′s′ test has been used for analysis. The probability of 5% was considered as significant for continuous variables such as age, period of gestation and birth weight. Odds ratio (OR) and confidence interval (CI) with 95% probability were determined. Results: The incidence of bacterial vaginosis was 41 in 200 patients. Adverse outcomes such as preterm labor, PROM and fetal complications were found more in pregnant women who had bacterial vaginosis (N=41), bacterial vaginosis with UTI (N=14) as compared to those without bacterial vaginosis (N=118). Conclusions: The incidence of poor pregnancy outcome was higher in bacterial vaginosis with UTI. Prevention of BV and UTI is cost effective to minimize the pregnancy-related complications and preterm labor to decrease in perinatal and maternal mortality and morbidity. We recommend all antenatal patients should be screened for the presence of bacterial vaginosis, other infections and UTI.